Kapitał zakładowy w spółce z ograniczoną odpowiedzialnością = Share capital of the limited liability company - Agata Klimczyk (Journal of Education, Health and Sport, 2015)
Klimczyk Agata. Kapitał zakładowy w spółce z ograniczoną odpowiedzialnością = Share capital of  the limited liability company. Journal of Education, Health and Sport. 2015;5(12):767-774. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51106